Method for manufacturing a joint body and a joint body
The water vapor plasma treatment method allows for flexible and durable bonding of conductive materials, addressing the challenge of coarse surfaces in ultra-thin devices by ensuring reliable joint formation and maintaining high optical transmittance.
Patent Information
- Application Number
- JP2021006995
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-20
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2041-01-20
AI Technical Summary
Existing methods for joining conductive materials, such as those used in ultra-thin devices like organic solar cells and LEDs, fail to maintain high flexibility due to increased thickness and require smooth surfaces, which are often coarse in these devices.
A method involving water vapor plasma treatment is applied to the surfaces of conductive materials to facilitate joining, followed by contact under pressure, which activates the surfaces and allows for bonding even with rough surfaces.
The method enables reliable joining of conductive materials with high flexibility and stability, even with coarse surfaces, suitable for applications requiring high optical transmittance and durability.
Smart Images

Figure 0007625248000001 
Figure 0007625248000002 
Figure 0007625248000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for joining conductive materials such as metals and semiconductor materials. (Method of Manufacturing Joint) and a joined body having a joined portion joined by said joining method. [Background technology]
[0002] One of the characteristics of thin devices (ultra-thin devices) that have organic solar cells, organic LEDs, etc. is their flexibility, and in order to put thin devices to practical use, it is important to have technology that can bond films (sheets) together while maintaining their flexibility. Here, we consider a system that includes multiple thin devices, such as a system that uses electricity generated by organic solar cells to light an organic LED. In order to put such a system to practical use, when bonding the electrodes of multiple thin devices, it is desirable to bond them in a way that shows high flexibility even between the thin devices (at the bonding parts).
[0003] As a method for joining conductive materials together, a method using a conductive adhesive (solder, ACF (Anisotropic Conductive Film), ACA (Anisotropic Conductive Adhesive), etc.) is known. However, such a joining method increases the thickness of the joint, and it is not possible to obtain high flexibility at the joint.
[0004] Other bonding methods are described in Patent Documents 1 and 2. Specifically, Patent Document 1 describes FAB bonding and bonding by oxygen plasma treatment, and Patent Document 2 describes bonding by water vapor plasma treatment. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2014-219685 A [Patent Document 2] International Publication No. 2018 / 159257 Summary of the Invention [Problem to be solved by the invention]
[0006] Patent Document 1 describes joining metals together, but the joining method described in Patent Document 1 cannot join metals together unless the surfaces of the metals to be joined are extremely flat (smooth). The surfaces of conductive materials provided in thin devices (ultra-thin devices) are often rough, making it difficult to join such conductive materials together using the joining method described in Patent Document 1. Furthermore, Patent Document 2 describes joining polymers together and joining polymers to glass, but does not describe joining conductive materials together.
[0007] Therefore, the present invention provides a bonding method capable of bonding conductive materials such as metals and semiconductor materials even if the surfaces of the conductive materials are rough. (Method of Manufacturing Joint) The purpose is to provide. [Means for solving the problem]
[0008] The bonding method of the present invention includes a plasma treatment step of performing a water vapor plasma treatment on a surface of a first conductive material and a surface of a second conductive material, a contact step of bringing the surface of the first conductive material after the water vapor plasma treatment into contact with the surface of the second conductive material after the water vapor plasma treatment, and a leaving step of leaving the first conductive material and the second conductive material while the surface of the second conductive material is in contact with the surface of the first conductive material.
[0009] According to the present invention, by using a water vapor plasma treatment to bond conductive materials together, conductive materials can be bonded together even if their surfaces are rough. As described below, when an aqua plasma treatment is performed, OH groups are attached to the surface of the object. Usually, when bonding conductive materials together, the surface is treated to remove all impurities, and the idea of using an aqua plasma treatment, which intentionally attaches OH groups that can become impurities, to bond conductive materials together is not usually conceived. At the same time, when bonding conductive materials together, attention is usually paid to how to make the surfaces as smooth as possible. Therefore, the problem of the present invention, which is to provide a method for bonding even when the surfaces are rough, rather than smoothing the surfaces, is not usually recognized by those skilled in the art.
[0010] Here, in the contacting step, the surface of the second conductive material may be overlapped on the surface of the first conductive material. In the contacting step, the surface of the second conductive material may be overlapped on the surface of the first conductive material, and pressure may be applied to at least one of the first conductive material and the second conductive material. By applying pressure, the second conductive material can be sufficiently contacted with the first conductive material, and the bonding between the first conductive material and the second conductive material can be more reliably achieved.
[0011] In the contact step, the surface of the first conductive material may be brought into contact with the surface of the second conductive material in the atmosphere, and in the leaving step, the first conductive material and the second conductive material may be left in the atmosphere. This makes it easier to perform the contact step and the leaving step.
[0012] The first conductive material may be a metal or a semiconductor material and the second conductive material may be a metal or a semiconductor material. The first conductive material may be gold, silver or copper and the second conductive material may be gold, silver or copper.
[0013] The method may further include a first forming step of forming an adhesion layer on a thin film substrate, forming a layer of the first conductive material on the adhesion layer to obtain a first thin film member, and a second forming step of forming an adhesion layer on a thin film substrate, forming a layer of the second conductive material on the adhesion layer to obtain a second thin film member, in which the plasma processing step may perform the water vapor plasma processing on a surface of the first thin film member on which the first conductive material is formed and a surface of the second thin film member on which the second conductive material is formed, and in the contacting step, the surface of the first thin film member after the water vapor plasma processing may be brought into contact with the surface of the second thin film member after the water vapor plasma processing. The adhesion layer may be a chromium layer.
[0014] In the first forming step, the adhesion layer and the layer of the first conductive material may be formed by vacuum deposition, and in the second forming step, the adhesion layer and the layer of the second conductive material may be formed by vacuum deposition. According to the present invention, even if a layer having a rough surface is formed by vacuum deposition, it is possible to bond conductive materials to each other.
[0015] In the contact step, a plurality of lines of the first conductive material may be contacted with a plurality of lines of the second conductive material so as to cross each other. In this way, a lattice having extremely high light transmittance can be obtained by joining the first conductive material and the second conductive material. Such a lattice is expected to be used for wiring on a touch panel screen, wiring on a light-emitting surface of a lighting device, and the like.
[0016] The present invention may be understood as a bonded body (such as a circuit board) having a bonded portion bonded by the above bonding method. The bonded portion bonded by the above bonding method has two types of regions having two types of oxygen concentrations. Therefore, the present invention is a bonded body (such as a circuit board) having a bonded portion bonded by the above bonding method. The present invention may be understood as a bonded body having a bonded portion where a material is bonded to a material, and the bonded portion has two types of regions each having two types of oxygen concentrations. The present invention may be understood as a bonding apparatus including a plasma generating unit that generates water vapor plasma and performing bonding by the above bonding method. Effect of the Invention
[0017] According to the present invention, conductive materials such as metals and semiconductor materials can be bonded to each other even if the surfaces of the conductive materials are rough. [Brief description of the drawings]
[0018] [Figure 1] 1(A) and 1(B) are diagrams showing an example of a bonding method. [Diagram 2] 2(A) and 2(B) are diagrams showing an example of a method for producing a thin film sample. [Diagram 3] 3(A) to 3(C) are diagrams showing an example of a bonding experiment. [Figure 4] FIG. 4(A) is a diagram showing an example of an SEM image showing a cross-section of a boundary portion between metal layers, and FIG. 4(B) is a diagram showing an example of an AFM image showing a cross-section of a boundary portion between metal layers. [Diagram 5] FIG. 5(A) shows an example of a STEM image showing a cross-section of the boundary between metal layers, and FIG. 5(B) shows the results of elemental analysis performed when obtaining the STEM image of FIG. 5(A). [Figure 6] 6(A) and 6(B) are diagrams showing an example of a bonding result when argon plasma treatment is performed and an example of a bonding result when water vapor plasma treatment is performed. [Figure 7] FIG. 7(A) is a diagram showing an example of a method for evaluating the bondable area, and FIG. 7(B) is a diagram showing an example of the evaluation result of the bondable area. [Figure 8] FIG. 8A is a diagram showing an example of a method for evaluating the wiring width and wiring space, and FIG. 8B is a diagram showing an example of the evaluation results of the wiring width and wiring space. [Figure 9]9(A) to 9(J) are photographs showing examples of the evaluation results of flexibility. [Figure 10] 10(A) to 10(J) are diagrams illustrating examples of the evaluation results of flexibility. [Figure 11] FIG. 11A is a diagram showing an example of the results of the 8585 test, and FIG. 11B is a diagram showing an example of the results of the heating test. [Figure 12] FIG. 12 is a diagram showing an example of light transmission characteristics at a joint between metal layers. [Figure 13] FIG. 13 is a diagram showing an example of the arrangement of metal layers to be joined. [Figure 14] FIG. 14(A) is a diagram showing an example of an SEM image when silver is bonded to silver, and FIG. 14(B) is a diagram showing an example of an SEM image when gold and silver are bonded. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, an embodiment of the present invention will be described with reference to the drawings.
[0020] (background) Known methods for joining conductive materials (conductive films) together include a method using a conductive adhesive (solder, ACF (Anisotropic Conductive Film), ACA (Anisotropic Conductive Adhesive), etc.) (FIG. 1(A)). However, such a joining method increases the thickness of the joint, making it impossible to obtain high flexibility at the joint. In this embodiment, conductive materials (e.g., metals) are joined together without using an adhesive so that high flexibility can be obtained at the joint (FIG. 1(B)).
[0021] Surface activated bonding (SAB) and atomic diffusion bonding (ADB) are known as methods for joining metals together without using adhesives. In SAB, the surfaces of two metal samples are plasma-treated (e.g., Ar plasma treatment), and the plasma-treated surfaces are brought into contact with each other to form a bond. In this process, two metal samples are bonded together. In plasma treatment, impurity layers (such as oxide films or organic films) formed on the surfaces of the samples are removed and the surfaces are activated by bombarding the surfaces with ions or neutral atoms. In ADB, metal is sputtered onto the surfaces of two samples in a high vacuum, and the sputtered surfaces are brought into contact with each other, thereby bonding the metals formed on the two samples together.
[0022] However, these joining methods cannot join metals together unless the surfaces of the metals to be joined are extremely flat. The surfaces of conductive materials provided in thin devices (ultra-thin devices) are often rough, making it difficult to join such conductive materials together using these joining methods.
[0023] A bonding method using water vapor plasma treatment has been proposed as a bonding method for bonding polymers together or polymers to glass without using adhesives. The present inventors predicted that "this bonding method would generate not only surface activated bonding (SAB) but also hydrophilic bonding (bonding mediated by OH groups)." Based on this prediction, the present inventors conducted various experiments in the hope that "if conductive materials can be bonded together by performing water vapor plasma treatment, (1) conductive materials can be bonded together even if their surfaces are rough, and (2) conductive materials can be bonded together by mild (e.g., low-power and short-time) plasma treatment."
[0024] (Thin film sample creation) The present inventors prepared thin film samples (thin film members) for use in various experiments by the following method. First, a release layer 102, a thin film substrate 103, an adhesion layer 104, and a metal layer 105 were formed in that order on a glass substrate 101 (FIG. 2(A)). The method and materials for forming each layer are not particularly limited, but the release layer 102 is a layer of a release agent, and was formed by spin coating. A parylene substrate was formed as the thin film substrate 103 by chemical vapor deposition (CVD). As the adhesion layer 104, a layer of chromium (Cr) having a layer thickness (film thickness) of 2.5 to 5 nm was formed by vacuum deposition. Then, as the metal layer 105, a layer of gold (Au) having a layer thickness (film thickness) of 10 to 100 nm was formed by vacuum deposition. Next, a portion consisting of the thin film substrate 103, the adhesion layer 104, and the metal layer 105 was peeled off from the glass substrate 101 to obtain a thin film sample 100.
[0025] The thickness of the adhesion layer 104 is not particularly limited, and may be thicker than 5 nm or thinner than 2.5 nm. The thickness of the metal layer 105 is also not particularly limited. However, the thinner the metal layer, the easier it is to flatten the metal layer, and the flatter the metal layer, the easier it is to bond the metal layers together. The thinner the metal layer, the higher the flexibility of the bonded portion between the metal layers. Therefore, in order to make it easier to bond the metal layers together and to increase the flexibility of the bonded portion, it is preferable that the thickness of the metal layer 105 is 100 nm or less. Furthermore, the thicker the metal layer, the easier it is to conduct the bonded metal layers (conduct with lower resistance). Therefore, in order to make it easier to conduct the metal layers together, it is preferable that the thickness of the metal layer 105 is 1 nm or more. In other words, it is preferable that the thickness of the metal layer 105 is 1 nm or more and 100 nm or less. Furthermore, when the thickness of the two metal layers to be joined is 10 nm or more and 40 nm or less, the joining is completed the moment they are overlapped or within about a few seconds after they are overlapped. Therefore, from the viewpoint of processing efficiency, it is more preferable that the thickness of the metal layer 105 is 10 nm or more and 40 nm or less. The thickness of the metal layer 105 may be greater than 100 nm. For example, if the surface roughness Rms of the two metal layers to be joined can be suppressed to 10 nm or less, the metal layers can be joined without any problem even if their thickness is greater than 100 nm.
[0026] (Joining experiment) The present inventors conducted the following experiment as a bonding experiment for bonding conductive materials together. First, two thin film samples 100a and 100b prepared by the above-mentioned method were prepared, and water vapor plating was applied to the surfaces (metal layers 105a and 105b) of the thin film samples 100a and 100b, respectively. The Zuma treatment was performed (Figure 3(A)). The water vapor plasma treatment was performed using Aqua The procedure was carried out using a Plasma® cleaner under the following conditions: Gas flow rate: 12sccm Power: 50W Mode:PE mode Time: 40 seconds Pressure: 10Pa
[0027] Next, the surfaces (the surfaces of the metal layers 105a, 105b) of the two thin film samples 100a, 100b were brought into contact with each other (FIG. 3(B)), and the two thin film samples 100a, 100b were left in this state (FIG. 3(C)). As shown in FIG. 3(B), when the surfaces of the two thin film samples 100a, 100b were brought into contact with each other, one of the thin film samples 100a, 100b was placed on the other of the thin film samples 100a, 100b. The processes in FIG. 3(B) and 3(C) may be carried out in the air, which makes the process easier.
[0028] FIG. 4(A) shows an example of a SEM (Scanning Electron Microscope) image showing a cross section of the boundary between the metal layers 105a and 105b after the above experiment. From FIG. 4, it can be seen that voids (air gaps) have occurred in a few places, but the boundary surface has disappeared in many areas, and it can be confirmed that the metal layers 105a and 105b have been successfully bonded. FIG. 4(B) is an AFM (Atomic Force Microscope) image showing the surface of the metal layer 105a used to obtain the results of FIG. 4(A). 4(B) shows the surface before the experiment. As shown in FIG. 4(B), the surface roughness Rms of the metal layer 105a was very large (very rough) at 6.29 nm. The surface roughness Rms of the metal layer 105b was also approximately the same as the surface roughness Rms=6.29 of the metal layer 105a. Thus, with the bonding method of this embodiment, the metal layers 105a and 105b can be bonded together even if the surfaces of the metal layers 105a and 105b are rough.
[0029] When the surfaces of the two thin film samples 100a and 100b are brought into contact with each other, it is preferable to apply pressure to at least one of the two thin film samples 100a and 100b (the two metal layers 105a and 105b). By applying pressure, one of the metal layers 105a and 105b can be brought into sufficient contact with the other of the metal layers 105a and 105b, and the bonding of the metal layers 105a and 105b can be more reliably achieved. The time required for successful bonding ranges from a few seconds to about one day. The flatter the surfaces of the metal layers 105a and 105b are, the shorter the time required for successful bonding, and the rougher the surfaces of the metal layers 105a and 105b are, the longer the time required for successful bonding.
[0030] (Evaluation of bonding results) FIG. 5A shows an example of a STEM (Scanning Transmission Electron Microscope) image showing a cross section of the boundary portion between the metal layers 105a and 105b after the above experiment. FIG. 5B shows the results of elemental analysis performed when obtaining the STEM image of FIG. 5A. Areas 1 and 2 are regions at (near) the boundary surface of the metal layers 105a and 105b, and Areas 3 and 4 are regions inside the metal layers 105a and 105b. From the results of FIG. 5B, it can be seen that there are two types of regions with two different oxygen concentrations at the boundary portion (bonding portion). Specifically, Area 1 has an oxygen concentration higher than the oxygen concentration inside the metal layers 105a and 105b (Areas 3 and 4), and Area 2 has an oxygen concentration similar to the oxygen concentration inside the metal layers 105a and 105b. This result matches the above prediction that SAB and hydrophilic bonding occur. It is considered that in Area 1, where the oxygen concentration is high, the metal layers are bonded to each other by hydrophilic bonding, and in Area 2, where the oxygen concentration is similar to that inside the metal layers, the metal layers are bonded to each other by SAB.
[0031] (Compared to conventional bonding) Figures 6(A) and 6(B) show the results of bonding when argon plasma treatment was performed (conventional) and when water was used. 1 shows an example of a bonding result when steam plasma treatment is performed (this embodiment). The inventors prepared two types of thin film samples using the above-mentioned preparation method: a thin film sample with a flat surface of the metal layer (metal layer surface roughness Rms of 1.84 nm) and a thin film sample with a rough surface of the metal layer (metal layer surface roughness Rms of 6.29 nm). Then, for each of the two types of thin film samples, bonding using argon plasma treatment (conventional) and bonding using water vapor plasma treatment (this embodiment) were attempted using the same bonding method as in the above bonding experiment. After that, a comparison was made between the conventional bonding result and the bonding result of this embodiment using SEM images (cross-sections of the boundary between metal layers).
[0032] When the surface of the metal layer is flat, as shown in FIG. 6(A), both argon plasma treatment and water vapor plasma treatment succeeded in bonding the metal layers together. On the other hand, when the surface of the metal layer is rough, as shown in FIG. 6(B), voids were generated over almost the entire length of the boundary surface in the argon plasma treatment (conventional), and the metal layers could not be bonded together, but the boundary surface disappeared in the water vapor plasma treatment (present embodiment), and the metal layers were successfully bonded together. In this way, the bonding method of this embodiment can bond metal layers with surface roughness that cannot be bonded by the conventional bonding method. For example, it is considered that the conventional bonding method cannot bond metal layers with a surface roughness Rms of 2 nm or more, but the bonding method of this embodiment can be expected to bond metal layers with a surface roughness Rms of 10 nm or less.
[0033] (Area that can be joined) In order to investigate the minimum area of a bondable (conductive) metal layer, the inventors created multiple types of thin film samples with different metal layer areas using the above-mentioned method, and performed the above-mentioned bonding experiment for each type of thin film sample. Here, as shown in FIG. 7(A), multiple types of thin film samples with different areas of the ends of the metal layer (area of Y mm x Y mm) were created. Then, in the bonding experiment, the ends of the metal layers were overlapped. In this way, multiple bonding results with different areas of the area where the metal layers are bonded (bonding target area; area where the metal layers overlap) were obtained.
[0034] FIG. 7(B) shows the results of the above-mentioned multiple bonding. The horizontal axis of FIG. 7(B) shows the area of the region to be bonded, and the vertical axis of FIG. 7(B) shows the contact resistance in the region to be bonded. FIG. 7(B) also shows the bonding result (conventional) when ACF is used. As shown in FIG. 7(B), when ACF is used, when the area of the region to be bonded is smaller than 500 μm×500 μm, the contact resistance becomes very large and the metal layers are not electrically connected (bonding between the metal layers fails). On the other hand, with the bonding method of this embodiment, even if the area of the region to be bonded is reduced to 50 μm×50 μm, there is no large increase in contact resistance, and the metal layers can be electrically connected (bonding between the metal layers is successful). Thus, with the bonding method of this embodiment, bonding can be achieved in a smaller area than with the conventional bonding method.
[0035] (Wire width and spacing) The present inventors prepared a thin film sample having a plurality of wirings (lines) as a metal layer by the above-mentioned preparation method, as shown in Fig. 8(A), and performed the above-mentioned bonding experiment. In Fig. 8(A), wiring A is a metal layer, and wiring B is a metal layer joined to wiring A. Wiring C is a metal layer, and wiring D is a metal layer joined to wiring C. Wirings A to D have the same width (wiring width). Specifically, the present inventors prepared a plurality of types of thin film samples with different wiring widths and wiring intervals by the above-mentioned preparation method, in order to investigate the wiring width that can be bonded (conductive) and the wiring interval that can be insulated, and performed the above-mentioned bonding experiment for each type of thin film sample.
[0036] Figure 8(B) shows the result of bonding when the wiring width and spacing are 10 μm. The horizontal axis of Figure 8(B) shows the voltage applied between the wirings, and the vertical axis of Figure 8(B) shows the current flowing between the wirings. As shown in Figure 8(B), a current proportional to the voltage flows between wirings A and B, and the wirings can be made conductive (the wirings have been successfully bonded). In addition, Even if a voltage is applied, no current flows between A and wiring D, and the wirings are insulated from each other. Therefore, the bonding method of this embodiment makes it possible to bond high-precision wiring having a very small wiring width and a very small wiring interval.
[0037] (Flexibility) The inventors also conducted an experiment to confirm the flexibility of the joint. Specifically, an experiment was conducted in which the joint was placed on a protrusion to confirm whether the joint follows the shape of the protrusion. This experiment was conducted while changing the radius of curvature R of the protrusion in the range of 25 mm to 0.5 mm. Figures 9(A) to 9(J) are photographs showing an example of the experimental results. For ease of understanding, the photographs of Figures 9(A) to 9(J) are illustrated in Figures 10(A) to 10(J). Figures 9(A) to 9(E) and 10(A) to 10(E) show an example of the flexibility of the joint joined by the joining method of this embodiment, and Figures 9(F) to 9(J) and 10(F) to 10(J) show an example of the flexibility of the joint joined using ACF (conventional). As shown in Figures 9(A) to 9(E) and Figures 10(A) to 10(E), in the joining method of this embodiment, the joint follows the protrusions of all radii of curvature R from 25 mm to 0.5 mm. On the other hand, as shown in Figures 9(I), 9(J) and 10(I), 10(J), when ACF is used, the joint does not conform to the protrusions with a curvature radius R of 1 mm or 0.5 mm, resulting in floating parts. Thus, the joint method of this embodiment has superior flexibility to the joint method of the past.
[0038] (stability) The inventors also conducted an experiment to confirm the stability of the bonded portion bonded by the bonding method of this embodiment. Specifically, a high temperature and humidity test and a heating test were conducted. In this high temperature and humidity test, the temperature was 85° C. and the relative humidity was 85% (absolute humidity 298 g / m 3) and observed the change in the characteristics over time. In the heating test, the sample obtained in the bonding experiment was heated on a hot plate at 100°C and observed the change in the characteristics of the bonded part over time. In both the high temperature and humidity test and the heating test, the change in the electrical resistance of the bonded part over time was observed. Figure 11(A) shows the results of the high temperature and humidity test, and Figure 11(B) shows the results of the heating test. The horizontal axis of Figure 11(A) shows the time the sample was left in an environment of a temperature of 85°C and a relative humidity of 85%, and the horizontal axis of Figure 11(B) shows the time the sample was heated on a hot plate at 100°C. In both Figures 11(A) and 11(B), the vertical axis shows the electrical resistance of the contact part. As shown in Figures 11(A) and 11(B), the electrical resistance of the contact part hardly changed even after the high temperature and humidity test and the heating test, indicating high stability against temperature and humidity.
[0039] The inventors also conducted a bending test in which the contact portion was repeatedly bent in order to confirm the stability of the bonded portion bonded by the bonding method of this embodiment. Figure 11(C) shows the results of the bending test. The horizontal axis of Figure 11(C) indicates the number of bendings, and the vertical axis of Figure 11(C) indicates the electrical resistance of the contact portion. As shown in Figure 11(C), the electrical resistance of the contact portion hardly changed even after the bending test, indicating high stability (durability; mechanical stability) against repeated bending.
[0040] (summary) As described above, according to this embodiment, by using water vapor plasma treatment to bond conductive materials together, conductive materials can be bonded together even if their surfaces are rough. Here, consider a system including multiple thin devices, such as a system that uses power generated by an organic solar cell to light an organic LED. If the bonding method of this embodiment is used to bond the electrodes of multiple thin devices, a fully flexible system that shows high flexibility even between thin devices (bonding parts) can be constructed.
[0041] When aqua plasma treatment is applied, OH groups are attached to the surface of the object. Normally, when conductive materials are bonded to each other, the surfaces are treated to remove all impurities. However, aqua plasma treatment, which intentionally attaches OH groups that can become impurities, is not applied to conductive materials. The idea of using a method for bonding two conductive materials together is not usually conceived. At the same time, when bonding conductive materials together, attention is usually focused on how to make the surfaces as smooth as possible. Therefore, the object of the present invention, which is to provide a method for bonding surfaces that are rough rather than smoothing the surfaces, is not usually recognized by those skilled in the art.
[0042] The above-described embodiment is merely an example, and the present invention also includes aspects that can be obtained by appropriately modifying or changing the above-described embodiment within the scope of the gist of the present invention. For example, the present invention includes various aspects described below.
[0043] (Light projecting joint) The metal layer may be thinned so that the metal layer transmits light. The inventors have successfully bonded the metal layers together even when the thickness (film thickness) of the metal layer is several tens of nm (20 nm or 10 nm), and have confirmed that light transmits even at the bonded portion. FIG. 12 is a diagram showing an example of light transmission characteristics at the bonded portion. The horizontal axis of FIG. 12 indicates the wavelength of light, and the vertical axis of FIG. 12 indicates the light transmittance. As shown in FIG. 12, if the thickness of the metal layer is 20 nm or 10 nm, the light transmittance at the bonded portion is about 40%. Note that the thinner the metal layer, the higher the light transmittance, but from the viewpoint of electrical conductivity, etc., a thicker metal layer is preferable.
[0044] As shown in Fig. 13, a plurality of lines (wiring) of a metal layer may be brought into contact with a plurality of lines of another metal layer so as to cross each other. In this way, a lattice with extremely high light transmittance can be obtained as a lattice in which metal layers are joined together. For example, if the wiring width is 10 μm and the wiring spacing is 100 μm, a lattice that appears almost transparent to the human eye (a lattice with a light transmittance extremely close to 100%) can be obtained. Such a lattice is expected to be used for wiring on touch panel screens and wiring on the light-emitting surface of lighting devices.
[0045] (other metal layers) Although an example of bonding layers of gold (Au) has been described, it is believed that the bonding method of this embodiment can also bond other metal layers. Therefore, the inventors tried to bond metal layers using silver (Ag) instead of gold. FIG. 14(A) shows an example of an SEM image (cross section of the boundary between metal layers) in a case where two thin film samples both have a silver layer as the metal layer. FIG. 14(B) shows an example of an SEM image in a case where one of two thin film samples has a gold layer as the metal layer and the other of the two thin film samples has a silver layer as the metal layer. In both FIG. 14(A) and FIG. 14(B), the disappearance of the boundary surface can be confirmed, and it can be confirmed that the metal layers have been bonded. Thus, the bonding method of this embodiment can not only bond gold layers, but also bond silver layers and bond dissimilar metals such as gold and silver. Similarly, it is believed that bonding of the same metal or dissimilar metals will be successful even if layers of copper (Cu), platinum (Pt), aluminum (Al), etc. are used as the metal layer.
[0046] In addition, instead of a metal layer, layers of other conductive materials such as semiconductor materials, for example layers of silicon, silicon oxide, carbon, or oxide layers such as glass, sapphire, lithium tantalate, lithium niobate, or layers of gallium nitride, gallium arsenide, gallium phosphide, silicon carbide, etc., are also believed to be used to successfully join homogeneous and heterogeneous materials.
[0047] The present invention may be understood as a bonded body (such as a circuit board) having a bonded portion bonded by the above bonding method. The bonded portion bonded by the above bonding method has two types of regions each having two types of oxygen concentrations. Therefore, the present invention may be understood as a bonded body having a bonded portion in which a first conductive material and a second conductive material are bonded, in which two types of regions each having two types of oxygen concentrations exist in the bonded portion. The present invention may be understood as a bonding device that includes a plasma generating unit that generates water vapor plasma and performs bonding by the above bonding method. [Explanation of symbols]
[0048] 100, 100a, 100b: thin film sample 101: glass substrate 102: peeling layer 103: thin film substrate 104: adhesive layer 105, 105a, 105b: metal layers
Claims
1. A first forming step of forming an adhesion layer on a thin film substrate and forming a layer of a first conductive material on the adhesion layer to obtain a first thin film member; a second forming step of forming an adhesion layer on the thin film substrate and forming a layer of a second conductive material on the adhesion layer to obtain a second thin film member; a plasma treatment step of performing a water vapor plasma treatment on a surface of the first thin film member on which the first conductive material is formed and a surface of the second thin film member on which the second conductive material is formed; a contacting step of contacting the surface of the first thin film member after the water vapor plasma treatment with the surface of the second thin film member after the water vapor plasma treatment; a leaving step of leaving the first thin film member and the second thin film member in a state in which the surface of the second thin film member is in contact with the surface of the first thin film member; The method for producing a bonded body comprising the steps of:
2. In the contacting step, the surface of the second thin film member is overlapped on the surface of the first thin film member.
2. The method of claim 1 .
3. In the contact step, the surface of the second thin film member is placed on the surface of the first thin film member, and pressure is applied to at least one of the first thin film member and the second thin film member.
3. The method according to claim 1 or 2.
4. In the contacting step, the surface of the first thin film member is brought into contact with the surface of the second thin film member in the atmosphere; In the leaving step, the first thin film member and the second thin film member are left in the atmosphere. The method according to any one of claims 1 to 3.
5. the first conductive material is a metal or a semiconductor material; The second conductive material is a metal or a semiconductor material. The method according to any one of claims 1 to 4.
6. the first conductive material is gold, silver, or copper; The second conductive material is gold, silver, or copper. The method according to any one of claims 1 to 5.
7. The adhesion layer is a layer of chromium. The method according to any one of claims 1 to 6.
8. In the first forming step, the adhesion layer and the first conductive material layer are formed by vacuum deposition; In the second forming step, the adhesive layer and the second conductive material layer are formed by vacuum deposition. The method according to any one of claims 1 to 7.
9. In the contacting step, a plurality of lines made of the first conductive material are contacted with a plurality of lines made of the second conductive material so as to cross each other. The method according to any one of claims 1 to 8.
10. By generating a surface activated bond and a hydrophilic bond by the plasma treatment step, the contact step, and the leaving step, two types of regions having two types of oxygen concentrations are formed in a bonded portion including at least a part of a first conductive material and at least a part of a second conductive material. The method according to any one of claims 1 to 9.
11. A joint having a thin film substrate, an adhesion layer, a first conductive material, a second conductive material, an adhesion layer, and a thin film substrate in this order, wherein a joint portion includes at least a part of the first conductive material and at least a part of the second conductive material, and the joint portion has two types of regions each having two types of oxygen concentrations. zygote.
Citation Information
Patent Citations
Sputtering target, joint type sputtering target and method for producing the same
JP2007297654A
Method for manufacturing semiconductor substrate
JP2008135732A
System and method for low temperature plasma bonding
JP2008513975A
Bonding method and bonding system
JP2011249643A
Chip-on wafer bonding method and bonding device and structure including chip and wafer
JP2013243333A